A high fat diet increases influenza A virus-associated cardiovascular damage - Siegers,JY; Novakovic,B; Hulme,KD; Marshall,R; Bloxham,CJ; Thomas,WG; Reichelt,ME; Leijten,L; van,Run P; Knox,K; Sokolowski,KA; Tse,BWC; et al. (Journal of Infectious Diseases, 2020)
BACKGROUND: Influenza A virus (IAV) causes a wide range of extra-respiratory complications. However, the role of host factors in these complications of influenza virus infection remains to be defined. METHODS: Here, we sought to use transcriptional profiling, virology, histology and echocardiograms to investigate the role of a high fat diet in IAV associated cardiac damage. RESULTS: Transcriptional profiling showed that, compared to their low fat (LF) counterparts, mice fed a high fat (HF) diet had impairments in inflammatory signalling in the lung and heart after IAV infection. This was associated with increased viral titres in the heart, increased left ventricular mass and thickening of the left ventricular wall in IAV-infected HF mice compared to both IAV-infected LF mice and uninfected HF mice. Retrospective analysis of clinical trials revealed that cardiac complications were more common in patients with excess weight, an association which was significant in 2 out of 4 studies. CONCLUSIONS: Together, these data provide the first evidence that a high fat diet may be a risk factor for the development of IAV-associated cardiovascular damageand emphasises the need for further clinical research in this area.